Development of ZMYM2‐FGFR1 driven AML in human CD34+ cells in immunocompromised mice. Issue 4 (4th May 2016) - Ren, Mingqiang; Qin, Haiyan; Wu, Qing; Savage, Natasha M.; George, Tracy I.; Cowell, John K.
Abstract : Acute myelogenous leukemia (AML) has an overall poor survival rate and shows considerable molecular heterogeneity in its etiology. In the WHO classification there are >50 cytogenetic subgroups of AML, many showing highly specific chromosome translocations that lead to constitutive activation of individual kinases. In a rare stem cell leukemia/lymphoma syndrome, translocations involving 8p11 lead to constitutive activation of the fibroblast growth factor receptor 1 (FGFR1) kinase. This disorder shows myeloproliferative disease with almost invariable progresses to AML and conventional therapeutic strategies are largely unsuccessful. Because of the rare nature of this syndrome, models that faithfully recapitulate the human disease are needed to evaluate therapeutic strategies. The t(8;13)(p11;q12) chromosome translocation is most common rearrangement seen in this syndrome and creates a ZMYM2‐FGFR1 chimeric kinase. To understand more about the molecular etiology of AML induced by this particular rearrangement, we have created a model human CD34+ cells transplanted into immunocompromized mice which develop myeloproliferative disease that progresses to AML with a long (>12 months) latency period. As in humans, these mice show hepatospenomegaly, hypercellular bone marrow and a CD45 + CD34 + CD13+ immunophenotype. Molecular studies demonstrate upregulation of genes such as KLF4 and FLT3 that promote stemness, and overexpression of MYC, which is associated with suppression of myeloid cell differentiation. This murine model, therefore, provides an opportunity to develop therapeutic strategies against the most common subtype within these FGFR1 driven neoplasms and study the molecular etiology in more depth. Abstract : What's new? Rearrangements involving FGFR1 kinase lead to the development of an atypical myeloproliferative disorder that frequently progresses to acute myelogenous leukemia (AML). Conventional therapeutic strategies are largely unsuccessful, and because of the rare nature of this syndrome, models that faithfully mimic the human disease are needed. This is the first report of a transplantable, humanized model of FGFR1‐driven AML in immunocompromized mice. The disease is faithfully mimicked and molecular analysis shows genetic changes consistent with stem cell leukemias. The model provides a new tool to both better understand the molecular mechanisms underlying the primary human disease and develop novel therapeutic approaches.